2001
DOI: 10.3727/096504001108747521
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of α-Galactosylceramide, KRN7000, in Mice With the Melanoma B16 Hepatic Metastasis and Immunohistological Study of Tumor Infiltrating Cells

Abstract: Liver metastasis of primary tumors is clinically a major problem. We examined the antitumor activity of KRN7000, an α-galactosylceramide, in mice with liver metastasis of the B16 melanoma. KRN7000 significantly inhibited tumor growth in the liver, and its potency was similar to that of interleukin-12. The KRN7000 administration resulted in a high percentage of cured mice, which acquired tumor-specific immunity. To study what kinds of antitumor effector cells participated in killing tumor cells, we then perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 2 publications
2
74
0
Order By: Relevance
“…Several lines of evidence suggested that soluble factors produced by NKT cells activate NK cells to mediate the antitumor effects of ␣GalCer in vivo (12,22,23). Treatment of mice with ␣GalCer induced significant serum levels of IL-2, IL-4, IL-12, and IFN-␥ in a dose-dependent manner, and this correlated with augmented NK activity of hepatic mononuclear cells and marked growth inhibition of EL-4 lymphoma cells in liver (63).…”
Section: Figurementioning
confidence: 99%
“…Several lines of evidence suggested that soluble factors produced by NKT cells activate NK cells to mediate the antitumor effects of ␣GalCer in vivo (12,22,23). Treatment of mice with ␣GalCer induced significant serum levels of IL-2, IL-4, IL-12, and IFN-␥ in a dose-dependent manner, and this correlated with augmented NK activity of hepatic mononuclear cells and marked growth inhibition of EL-4 lymphoma cells in liver (63).…”
Section: Figurementioning
confidence: 99%
“…10,11 Treatment of mice with the NKT cell ligand a-GalCer has been shown to have an antitumor effect in tumor metastasis models of the liver, lung and lymph nodes. [12][13][14][15] This effect is most likely caused by subsequent activation of NK cells, CTL and antigen presenting cells. 16 In 2 clinical phase 1 trials in advanced cancer patients injected with a-GalCer 17 or a-GalCer-loaded immature dendritic cells, 18 a distinct activation of the immune system was observed, but only in cancer patients with detectable Va24 þ Vb11 þ NKT cell numbers.…”
Section: Vb11mentioning
confidence: 99%
“…K RN7000, a marine sponge glycolipid with a novel ␣-galactosylceramide (␣-GalCer) structure, was found to exhibit potent antitumor activity in a variety of experimental and spontaneous tumor metastasis models (1)(2)(3)(4)(5)(6)(7). The antitumor effects of ␣-GalCer were first shown to be attributable to natural killer (NK) cell activation and the antigen presentation function of dendritic cells (8).…”
mentioning
confidence: 99%